Medical student and resident perceptions when working together in resident continuity clinics. Issue 1 (1st January 2020) - Chaalan, Tina; Landis Lewis, Deborah; O'Connor, Kelly; Popp, Bryan; Hammoud, Maya; Mowers, Erika L
Summary: Background: Resident continuity clinics (RCCs), where residents see patients largely independently, is a common requirement for residency programs in the USA. Students often participate in these clinics but it is unknown how this effects resident learning or student satisfaction. Objective: This study aims to describe effects on the learning environment when students and residents work together in an RCC. Design: Separate surveys were administered to residents and students working at St. Joseph Mercy Hospital (SJMH) in Ann Arbor, Michigan, from 2016–2018. Results: Response rates were 79/116 (68.1%) for students and 21/24 (87.5%) for residents. A one-sample Wilcoxon signed rank test was used to test whether most five-level Likert-type scale responses were 'agree' or 'strongly agree.' Of medical students, 88.6% enjoyed working with residents (p < 0.001) with 60.8% indicating residents were effective teachers (p < 0.001). The majority of residents (85.7%) were neutral, agreed, or strongly agreed that they enjoyed working with students (p < 0.001). However, 61.9% of residents believed they were too busy to be effective teachers (p < 0.001). Conclusions: Both residents and students positively viewed their interactions in RCCs. Although most students felt residents were effective teachers, most residents worried about their ability to balance clinical care and teaching responsibilities.